The combined impact of neutrophil-percentage-to-albumin ratio and depressive symptoms on mortality in US arthritis patients: insights from NHANES (2005–2018) - Bai, Jinyue; Lv, Taihong; Yu, Hanming; Ji, Zishuo; Gu, Xiu; Gao, Yun; Ma, Li (Frontiers in Public Health, 2025)
BackgroundThe neutrophil-to-albumin ratio (NPAR) reflects inflammation and nutritional status, while depression significantly impacts survival in chronic disease patients. This study examines the independent and combined effects of NPAR and depressive symptoms on all-cause and cardiovascular mortality in arthritis patients.MethodsWe analyzed a nationally representative sample of people with arthritisaged 40 and older from NHANES (2005–2018). NPAR assessed inflammation and nutritional status, while depressive symptoms were measured by PHQ-9. Weighted Cox regression examined the independent and joint associations of NPAR and PHQ-9 with all-cause and cardiovascular disease (CVD) mortality.ResultsOur analysis indicated that higher NPAR levels combined with lower depressive symptoms (PHQ-9 < 10) significantly increased all-cause and CVD mortality risks in arthritis patients. In this group, the hazard ratio (HR) for all-cause mortality was 2.087, with a similarly elevated CVD mortality risk (HR = 2.614), underscoring NPAR’s predictive strength in non-depressed individuals. Among those with higher depressive symptoms, while elevated NPAR was still associated with increased mortality, its impact on CVD mortality was less marked, highlighting the need for further research into the NPAR-depression interaction.ConclusionThis study identifies NPAR as a key predictor of mortality in arthritis patients, particularly those with fewer depressive symptoms. NPAR significantly predicts all-cause and CVD mortality, underscoring its value as an inflammation and nutrition biomarker. Integrating NPAR in clinical practice could enhance individualized risk assessment and intervention for arthritis patients.